Organizacje pozarządowe w Polsce - problemy współpracy międzynarodowej - Iwankiewicz-Rak, Barbara (Non Government Organizations - Problems of International Co-operation, 2007)
The role of NGOs in modern market economy should be analyzed from the point of view of: provider of social goods, representative (advocate) of interests of social groups. The organizations are created as a response of the society to social needs unsatisfied by administration and government agencies. They are created on the social initiative in those spheres of services where public institutions failed offering insufficient level and quality of services. Non-governmental organizations need co-operation with the social, public and business environment. Creation of the co-operation in the region is a special area of local activities: with the local community with the public administration with business firms. The new role of NGOs in the process of integration of Europe was formally expressed in the Treaty of European Union signed in 1992 in Declaration 23 attached to the Treaty. This declaration resulted in the development of the co-operation of NGOs with the European Community Institutions and between social organizations of various countries, especially between NGOs in democratic countries and non-governmental organizations of Central and Eastern European countries. This paper presents results of a comparative analysis of development of NGO sector in Poland and in other European countries, done by using The NGO Sustainability Index which analyzes seven different dimensions of NGO sector as follows: legal environment, organizational capacity, financial viability, advocacy, service provision, infrastructure, public image.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 133-145